Urban Systems: Understanding and Predicting the Spatial Distribution of China's Population. Issue 4 (20th July 2021) - Li, Pengfei; Lu, Ming
Abstract: With urbanization and population migration, some Chinese cities fall into decline whereas others prosper. Using nighttime light data, we redefine the city based on economic function and evaluate the city size distribution in representative countries. The results provide evidence not only for Zipf's law, but also for a distortion in China's current city size distribution. This study proposes a feasible method to predict urban population distribution based on the role of geographical factors in regional development, following the idea of spatial equilibrium. This prediction suggests that the divergence of city size in China tends to be pronounced, with inter‐regional income disparity being narrowed and the city size distribution following Zipf's law. The Chinese government should further relax restrictions on population inflow into large cities and prepare for more migration in the future.